Cosmopolitical encounters: Prototyping at the National Zoo in Santiago, Chile. Issue 4 (4th July 2018) - Tironi, Martín; Hermansen, Pablo
ABSTRACT: This article presents an empirical reflection on how the prototyping of an environmental enrichment device for chimpanzees at the National Zoo of Chile precipitates a cosmopolitical encounter. Using material produced by design students, zookeepers and the chimps Judy and Gombe, we describe how prototyping iterations establish open processes of dialogue and encounters among humans and nonhumans. The case will demonstrate how prototyping can go further than the generation of models of an original. On the contrary, the cosmopolitical encounter emerging from the prototyping process makes evident a truly ontological vocation, acknowledging humans and other-than-human beings as singular entities. Its provisional and malleable nature turns this device into a privileged locus for the exploration of interspecies entanglement. Although zoos are scientifically organized institutions, in this case we observe how its anthropocentric hierarchy was performatively reshuffled at certain moments of the prototyping process. The cosmopolitical qualities of the prototyping process analyzed derive from its capacity to deploy an ethics of attention and care between the agencies at play, that is, for unfold gestures of mutual vulnerability. Finally, we propose prototyping as a device for moving from cosmopolitics as a way of understanding the world to cosmopolitics as a matter of design .